Multicenter validation of a bedside antisaccade task as a measure of executive function. - Hellmuth J; Mirsky J; Heuer HW; Matlin A; Jafari A; Garbutt S; Widmeyer M; Berhel A; Sinha L; Miller BL; Kramer JH; Boxer AL; et al. (Neurology, 2012)
Objective: To create and validate a simple, standardized version of the antisaccade (AS) task that requires no specialized equipment for use as a measure of executive function in multicenter clinical studies.Methods: The bedside AS (BAS) task consisted of 40 pseudorandomized AS trials presented on a laptop computer. BAS performance was compared with AS performance measured using an infrared eye tracker in normal elders (NE) and individuals with mild cognitive impairment (MCI) or dementia (n = 33). The neuropsychological domain specificity of the BAS was then determined in a cohort of NE, MCI, and dementia (n = 103) at UCSF, and the BAS was validated as a measure of executive function in a 6-center cohort (n = 397) of normal adults and patients with a variety of brain diseases.Results: Performance on the BAS and laboratory AS task was strongly correlated and BAS performance was most strongly associated with neuropsychological measures of executive function. Even after controlling for disease severity and processing speed, BAS performance was associated with multiple assessments of executive function, most strongly the informant-based Frontal Systems Behavior Scale.Conclusions: The BAS is a simple, valid measure of executive function in aging and neurologic disease.